Compensating for missing data in the OHRKAN cohort study examining total leisure noise exposure among adolescents. (1st July 2022) - Wendl, Johannes; Gerstner, Doris; Huß, Jonas; Weilnhammer, Veronika; Jenkac, Christina; Pérez-Àlvarez, Carmelo; Steffens, Thomas; Herr, Caroline; Heinze, Stefanie
Abstract: Objective: Investigating determinants of total leisure noise (TLN) exposure among adolescents over 7.5 years and compensating for missing data due to loss to follow-up. Design: In the OHRKAN cohort study, data were collected by questionnaires at four waves. TLN was calculated from self-reported duration spent participating in 18 leisure activities. High exposure was defined as exceeding 85 dB(A) of equivalent continuous average sound pressure level (SPL) during a 40-h week. Multiple imputation (MI) and generalised estimating equations (GEE) were used to analyse odds ratios (OR) of determinants of TLN exposure and compared to complete-case analysis. Study sample: Closed cohort of 2148 students enrolled in grade 9 of any school in Regensburg (Germany), recruited from 2009 to 2011. Results: Up to 74% of adolescents had risky TLN exposure, depending on wave. The most significant sources were discotheques, portable listening devices (PLD) and stereo systems. Higher TLN exposure was associated with time point, education, single-parent households and gender. MI under MAR assumption changed results only slightly compared to complete-case analysis. Conclusions: Prevalence of risky TLN is high during adolescence. MI reinforced trends detected in former results of OHRKAN. Preventive measures should consider the main drivers of noise exposure including changes by age and high risks groups.